Strategic initiatives to improve tobacco cessation delivery in India - Rakesh Gupta; Mira B Aghi; Arpit Gupta; Garima Bhatt; Sonu Goel (Wolters Kluwer Medknow Publications, 2022)
Background: Globally, India is recognized for providing comprehensive coverage of tobacco cessation through the infrastructure and resources over the last two decades. Nevertheless, its current tobacco burden is worrying due to an increase in ~2 million initiators and 5.87% tobacco related deaths annually. Objective: It was to identify and describe challenges and barriers in tobacco cessation delivery that exist at various levels of health care as well as at the level of tobacco users, their care givers and communities in which they live. Method: Besides authors' first-hand collective experience in the tobacco control for over 80 years and ~35 years in tobacco cessation and reviewed references, the stakeholders communications during various events along with telephonic or in-person with some of them were assimilated to comprehend an overall understanding of the issue. Results: The challenges and barriers are primarily due to low priority assigned by the relevant functionaries, the inadequacy of resources, poor engagement of health-and insurance-sectors and healthcare workers, a low intent to quit by its users, suboptimal and discontinuous enforcement of the Cigarette and Other Tobacco Products Act of 2003 (COTPA), and indifference of the non-users. Conclusion: The countrywide strategic initiatives required "as a package" should include political and bureaucratic commitment, mass communication on benefits of quitting, licensed current users quitting through a timeline, use of systems approach in tobacco cessation delivery, implementation, and enforcement of vendor licensing and the proposed amendments in COTPA. Their perceived benefits will become a win-win situation for all stakeholders engaged in tobacco cessation delivery.